2021
DOI: 10.1021/acs.jpcc.1c07674
|View full text |Cite
|
Sign up to set email alerts
|

Flux-Assisted Low Temperature Synthesis of SnNb2O6 Nanoplates with Enhanced Visible Light Driven Photocatalytic H2-Production

Abstract: Foordite SnNb 2 O 6 as a typical layered niobate has gained great attention in photocatalytic applications owing to its narrow band gap and proper conduction and valence band potentials. However, the ever reported methods toward the synthesis of SnNb 2 O 6 nanostructures required either the use of environmentally unfriendly solvents or a prolonged high temperature heat treatment. Herein, we develop a facile flux-assisted low temperature synthesis route for the preparation of SnNb 2 O 6 nanoplates by using H 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It could be provided that the photo-generated electrons were trapped by the PMS efficiently, which was consistent well with the report in the literature. 58–60…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be provided that the photo-generated electrons were trapped by the PMS efficiently, which was consistent well with the report in the literature. 58–60…”
Section: Resultsmentioning
confidence: 99%
“…It could be provided that the photo-generated electrons were trapped by the PMS efficiently, which was consistent well with the report in the literature. [58][59][60] In order to study the electron transfer process between Fe(III) and Fe(II), the cyclic voltammetry (CV) behaviors of FeWO 4 on electrodes were investigated in a mixed solution of 0.5 mol L À1 Na 2 SO 4 and 0.2 mmol PMS. Fig.…”
mentioning
confidence: 99%
“…Tin­(II) niobate (SnNb 2 O 6 ), which possesses the possible band position to allow overall water splitting, can absorb visible light at up to ca. 540 nm (2.3 eV) by contributing to the hybridization between Sn 5s and O 2p orbitals. , Hence, SnNb 2 O 6 has been developed by various methods including solid-state synthesis, , flux-assisted synthesis, microwave-assisted synthesis, solvothermal synthesis, and hydrothermal synthesis , (the synthesis method, precursors, and band gap energy of SnNb 2 O 6 previously reported and in the present study are summarized in Table S1). It has been reported that SnNb 2 O 6 enables H 2 and O 2 evolutions from aqueous solutions containing sacrificial reagents under visible light irradiation (>420 nm) and that the photocatalytic activity of SnNb 2 O 6 depends on the existence of tetravalent tin (Sn 4+ ) on the surface. , Actually, cobalt oxide (CoO x ) cocatalyst loading suppresses the oxidation of Sn 2+ on the SnNb 2 O 6 surface, and it enables highly efficient O 2 evolution from water .…”
Section: Introductionmentioning
confidence: 82%
“…In recent years, Sn-based photocatalysts, such as SnO 2 , Sn 3 O 4 , SnS 2 , SnSe, Cu 3 SnS 4 , and SnNb 2 O 6 , have been developed in many fields of photocatalysis, attributed to its suitable band gap, high redox capacity, and long-term stability. Among them, SnO 2 is a better electron generator than TiO 2 , ascribed to its more positive conductive band (CB) edge .…”
Section: Introductionmentioning
confidence: 99%